Facing hazards and disasters : understanding human dimensions (National Academies Press, 2006)
"Social science research conducted since the late 1970's has contributed greatly to society's ability to mitigate and adapt to natural, technological, and willful disasters. However, as evidenced by Hurricane Katrina, the Indian Ocean tsunami, the September 11, 2001 terrorist attacks on the United States, and other recent events, hazards and disaster research and its application could be improved greatly. In particular, more studies should be pursued that compare how the characteristics of different types of events--including predictability, forewarning, magnitude, and duration of impact--affect societal vulnerability and response. This book includes more than thirty recommendations for the hazards and disaster community"--Publisher's description